Antarctic palaeo-ice streams - Livingstone, Stephen J.; Cofaigh, Colm O.; Stokes, Chris R.; Hillenbrand, Claus-dieter; Vieli, Andreas; Jamieson, Stewart S. R. (Earth-Science Reviews, 2012)
We review the geomorphological, sedimentological and chronological evidence for palaeo-ice streams on the continental shelf of Antarctica and use this information to investigate basal conditions and processes, and to identify factors controlling grounding-line retreat. A comprehensive circum-Antarctic inventory of known palaeo-ice streams, their basal characteristics and minimum ages for their retreat following the Last Glacial Maximum (LGM) is also provided. Antarctic palaeo-ice streams are identified by a set of diagnostic landforms that, nonetheless, display considerable spatial variability due to the influence of substrate, flow velocity and subglacial processes. During the LGM, palaeo-ice streams extended, via bathymetric troughs, to the shelf edge of the Antarctic Peninsula and West Antarctica, and typically, to the mid-outer shelf of East Antarctica. The retreat history of the Antarctic Ice Sheet since the LGM is characterised by considerable asynchroneity, with individual ice streams exhibiting different retreat histories. This variability allows Antarctic palaeo-ice streams to be classified into discrete retreat styles and the controls on grounding-line retreat to be investigated. Such analysis highlights the important impact of internal factors on ice stream dynamics, such as bed characteristics and slope, and drainage basin size. Whilst grounding-line retreat may be triggered, and to some extent paced, by external (atmospheric and oceanic) forcing, the individual characteristics of each ice stream will modulate the precise timing and rate of retreat through time.